ANALISIS TINGKAT KESEHATAN BANK TERHADAP KINERJA KEUANGAN MENGGUNAKAN METODE RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNING DAN CAPITAL(RGEC) (STUDI KASUS BANK MUAMALAT TAHUN 2020) - Mayang Sari (Program Studi Perbankan Syariah, 2022)
The existence of Islamic banking in the archipelago has received recognition after the issuance of the Banking Law NO. 7 of 1992 which was revised through Law NO.10 of 1998, which explicitly recognizes the existence and functioning of profit-sharing banks or better known as Islamic banks. Thus, an Islamic Bank is a bank that operates on the principle of profit sharing. This study aims to determine how the Bank's soundness level on financial performance by using the RGEC method at Bank Muamalat Indonesia in 2020. This study uses a descriptive quantitative method with a literature study approach and the type of data used is secondary data sourced from the financial statements of PT. Bank Muamalat Indonesia 2020. The results of this study show that in 2020 PT. Bank Muamalat Indonesia is in the fairly healthy category with a CAR ratio of 15.21%, NPF 3.95%, FDR 70.21%, ROA 0.029% and ROE 1.604% where the values ??????in the composite ranking table are overall at composite rank 3 which making Bank Muamlata Indonesia in the